Islam, Etika Hukum dan Legal Culture - Author: Yusdani (Unisia, 2005)
The main problem of Indonesia as a nation is a multidimensional crisis. This problem emerges because of misleading management of this state. The misleading manage ment drives many cases, for instance corruption culture. The corruption denotes main problem in this nation building. Meanwhile when Indonesia towards reformation era since 1996, paying attention to law action and law enforcement is more than that ofjurisprudence. Instead, it is still rarely the investigation of jurisprudence regarding religion and real culture of this nation. Because of Indonesian are religious nation, the religious leaders in Indonesia can contribute to formulate the ethic of law material, the ethic of law enforcement, and that of law institution.